The Effect of Natural Gas Reserves in the Eastern Mediterranean on Regional Energy Policies and Competition - Yaşa, A. Gökhan; Yılmaz, Mutlu (Fırat University, 2022)
The study examines the energy resources specific to the Eastern Mediterranean region in the context of regional energy policies. Although natural gas is already an important energy source, its importance is increasing day by day in our world. This situation showed itself with new regional developments and was felt especially in the Eastern Mediterranean region. With the recent developments, the importance of natural gas has also increased for Turkey. In this context, the reserve status of natural gas in the world as an energy source has been considered, and it has also been interpreted together with data such as its production, import and export in the world. Then, the Eastern Mediterranean issue was examined and in this context, historical developments that have taken place so far have been discussed. In the light of historical developments, energy competition in the Eastern Mediterranean region has also been analyzed. In particular, the interest and needs of the countries in the region in this field were also evaluated. However, also assessed other chronic particularly concerned with reflections on the problems of energy competition between Turkey and Greece. Finally, implications were made about how the potential gas in the region could be used. The proper utilization of this potential will protect the environment of peace that will increase regional prosperity and stability.

Çalışma Doğu Akdeniz Bölgesi özelinde bulunan enerji kaynaklarını bölgesel enerji politikaları bağlamında incelemektedir. Doğalgaz zaten önemli bir enerji kaynağı olmakla birlikte her geçen gün dünyamızda önemini gittikçe arttırmaktadır. Son dönemde yaşanan gelişmelerle birlikte Türkiye için de doğalgazın önemi artmıştır. Bu durum kendisini yeni bölgesel gelişmeler ile göstermiş olup özellikle Doğu Akdeniz bölgesinde hissedilmiştir. Bu kapsamda bir enerji kaynağı olarak doğalgazın dünyadaki rezerv durumu ele alınmış bununla birlikte dünyadaki üretimi, ithalatı, ihracatı gibi verilerle birlikte de yorumlanmıştır. Daha sonra ise Doğu Akdeniz konusu irdelenmiş bu kapsamda şu ana kadar gerçekleşmiş tarihsel gelişmeler ele alınmıştır. Tarihsel gelişmeler ışığında Doğu Akdeniz’de oluşan enerji rekabeti de analiz edilmiştir. Özellikle bölge ülkelerinin bu sahaya olan ilgisi ve ihtiyaçları da değerlendirmeye alınmıştır. Bununla birlikte özellikle Türkiye ve Yunanistan arasında olan diğer kronik sorunların söz konusu enerji rekabetine yansımaları da değerlendirilmiştir. Son olarak ise bölgedeki potansiyel gazın nasıl kullanılabileceği ile ilgili çıkarımlar yapılmıştır. Bu potansiyelin doğru şekilde değerlendirilmesi bölgesel refahı, istikrarı arttıracak barış ortamını koruyacaktır.
DOĞU AKDENİZ’DE BULUNAN DOĞALGAZ REZERVLERİNİN BÖLGESEL ENERJİ POLİTİKALARINA VE REKABETE ETKİSİ